2001
DOI: 10.1103/physrevb.63.174430
|View full text |Cite|
|
Sign up to set email alerts
|

Ground-state phase diagrams of frustrated spin-SXXZchains: Chiral ordered phases

Abstract: The ground-state phase diagram of the frustrated spin-S XXZ chain with the competing nearestand next-nearest-neighbor antiferromagnetic couplings is studied numerically by using the densitymatrix renormalization-group method for the cases of S = 1/2, 3/2, and 2. We are paricularly interested in the possible gapless and gapped chiral phases, in which the chiralityexhibits a finite long-range order whereas the spin correlation decays either algebraically or exponentially. We show that the gapless chiral phase ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 33 publications
(24 reference statements)
1
23
0
Order By: Relevance
“…The remaining (φ + ,θ + ) sector induces the gapless behavior of longitudinal-spin and nematic correlation functions. On the other hand, the c 2 term is known to induce a vector chiral phase [53][54][55] with (S j × S j +1 ) z ∼ sin( √ 2πθ − ) = 0 in a lower-field regime. 8,53 Let us concentrate on the former nematic TL liquid in the following.…”
Section: Effects Of the Dm Interactionmentioning
confidence: 99%
“…The remaining (φ + ,θ + ) sector induces the gapless behavior of longitudinal-spin and nematic correlation functions. On the other hand, the c 2 term is known to induce a vector chiral phase [53][54][55] with (S j × S j +1 ) z ∼ sin( √ 2πθ − ) = 0 in a lower-field regime. 8,53 Let us concentrate on the former nematic TL liquid in the following.…”
Section: Effects Of the Dm Interactionmentioning
confidence: 99%
“…[32][33][34]38,39 In this case, due to the anisotropy, symmetry of the system in spin space is lowered from isotropic SU͑2͒ to U͑1͒ ϫ Z 2 , where the U͑1͒ and Z 2 symmetries correspond to the rotation in the easy plane and the sign of pitch angle of helical spin order, respectively. While the continuous U͑1͒ symmetry is preserved in the quantum case s = ͉s͉ Ͻϱ, 40 the discrete Z 2 symmetry can be spontaneously broken even in the quantum limit s = 1 2 , thereby resulting in the vector chiral phase.…”
Section: Introductionmentioning
confidence: 98%
“…It is also known that the model exhibits a long-range order ͑LRO͒ of vector chirality in the case of anisotropic exchange couplings. [32][33][34] With applied magnetic field, the phase diagram becomes even richer. From numerical studies of the magnetization process, it has been found that for a certain range of J 2 / J 1 the magnetization curve exhibits a plateau at one third of the saturated magnetization and cusp singularities.…”
Section: Introductionmentioning
confidence: 98%
“…Spin systems with two-body interactions in such ladders have been studied extensively both numerically and analytically [29][30][31][32], at half filling [33,34], and with magnetic fields in the ferromagnetic [35] and antiferromagnetic regimes [36,37]. Model (1) presents no exact solution except for W = t = 0 for which there exists a SF to CDW phase transition at V = 2t [38] and for W = V = 0 for which the ground state can be obtained exactly at t = −t/2 [24].…”
Section: Modelmentioning
confidence: 99%